A new Givetian athyridid species from northwest Africa discovered by three-dimensional reconstruction of shell morphology of internal molds. (July 2014) - Schemm-Gregory, Mena
Abstract : A new method of analyzing the internal shell morphology (including the complete brachidium of internal molds) of articulated brachiopod shells through the use of serial sections and digital three-dimensional reconstruction is presented. The method introduced is essential for the study of internal shell structures such as brachidia, or cardinalia, if computed tomography (CT) is not suitable or if a CT scanner is not available. A new species of Athyris from Givetian beds of Northwest Africa was selected to exemplify this method. To compare this species with figured serial sections in the literature, two-dimensional drawings of grinding surfaces are provided. Athyris africana n. sp. is only preserved as internal molds of articulated specimens. The new species is included in the evolutionary lineage of the group around Athyris concentrica . The faunal assemblage of A. africana n. sp. shows affinities to Western European and North American brachiopod faunas.